Performance and enzymatic activities of the bullfrog tadpoles - Filho, José Teixeira de Seixas; Oliveira, Maria Goreti Almeida; Moura, Guilherme de Souza; Garcia, Silvana Lages Ribeiro; Lanna, Eduardo Teixeira Arruda; Silva, Lilia Nogueira da (Pesquisa Agropecuaria Brasileira, 2008)
The objective of this study was to evaluate the performance and the digestive enzyme activity in bullfrog tadpoles, fed with commercial ration during 60 days, at the density of one tadpole per liter in 30 L boxes. The parameters measured fortnightly were: survival, length, weight, ration consumption, and amylase, lipase and trypsin activities. There larger growth of the tadpoles occurred from the 15th to the 45th day – 20.61 mm. During the first 15 days, the tadpoles had the largest specific growth rate, 16.7% per day. From the 45th to the 60th day, the tadpoles had the largest weight gain, 3.98±0.73 g, the largest ration consumption, 14.40±1.14 g and the best feed conversion, 3.67:1.0±0.18. There was significant increase in enzyme activities after the 30th day. Relationships were observed between the specific enzyme activities and the different development phases of the tadpoles.
Keywords: Lithobathes catesbeianus; enzymology; bullfrog farming; morphophysiology; animal nutrition; tadpole production